2014
DOI: 10.1002/anie.201308554
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Driven Chiral‐Interaction Reversion for Organogel Formation

Abstract: For chiral gels and related applications, one of the critical issues is how to modulate the stereoselective interaction between the gel and the chiral guest precisely, as well as how to translate this information into the macroscopic properties of materials. Herein, we report that this process can also be modulated by nonchiral solvents, which can induce a chiral-interaction reversion for organogel formation. This process could be observed through the clear difference in gelation speed and the morphology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…[7] Up to now, much attention has been paid to the design and synthesis of these stimuli-responsive supramolecular hydrogels,i ncluding synthetic polymers [8] and low-molecular-weight gelators (LMWGs). [9] Fore xample,T ong et al have reported ad ual redox-and light-responsive hydrogel system based on the supramolecular complexation between poly(acrylic acid) and ferric ions in the presence of citric acid. [10] Recently we have showed as imilar quadruple stimuli-responsive supramolecular hydrogel based on the LMWG with ferrocenyl groups integrated in the molecular backbones.…”
mentioning
confidence: 99%
“…[7] Up to now, much attention has been paid to the design and synthesis of these stimuli-responsive supramolecular hydrogels,i ncluding synthetic polymers [8] and low-molecular-weight gelators (LMWGs). [9] Fore xample,T ong et al have reported ad ual redox-and light-responsive hydrogel system based on the supramolecular complexation between poly(acrylic acid) and ferric ions in the presence of citric acid. [10] Recently we have showed as imilar quadruple stimuli-responsive supramolecular hydrogel based on the LMWG with ferrocenyl groups integrated in the molecular backbones.…”
mentioning
confidence: 99%
“…[ 77 ] Intensive studies of this domain may offer an alternative platform utilized in the enantiomeric separations, and further facilitate the understanding of the self-assembly behavior of chiral gelators in natural systems.…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 77 ] Copyright 2014, Wiley-VCH. Liquid separation systems made of homogeneous copolymer fi lms with controlled surface wettability.…”
Section: Application To Our Daily Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our lab tried to solve one of the critical issues about chiral organogels: how to precisely modulate the stereoselective interaction between chiral organogels and chiral guests, as well as how to translate it into the macroscopic properties of materials. [ 64 ] For this purpose, dipeptides were selected as the key unit of gelator owing to their abundant H-bonding sites and programmable sequence combinations (Figure 7 c). A para -disubstituted phenyl group was used to connect two dipeptide arms.…”
Section: Biomolecular Recognition and Testingmentioning
confidence: 99%